The effect of hematocrit and punch location on assay bias during quantitative bioanalysis of dried blood spot samples. (October 2011) - O''Mara, M; Hudson-Curtis, B; Olson, K; Yueh, Y; Dunn, J; Spooner, N
Background: Dried blood spot (DBS) sampling, the collection of whole blood samples on paper, is being evaluated for its use in quantitative analysis. The aim of this investigation was to evaluate the impact of sample hematocrit (HCT) and punch location on assay bias in the measurement of compounds with varying physicochemical properties, when a portion of a DBS sample is analyzed. In addition, the statistical significance of factors such as compound, card type, HCT level, spot position on a card and the location of the punch on the spot were evaluated.Results: The results of this work indicate that for quantitative analysis using a portion of the DBS, notable bias (>15%) exists due to the effect of HCT and nonhomogeneous distribution of compound across the spot. The statistical analysis of results from a split-split-plot designed study showed that the factors of compound, card type and HCT were statistically significant (p < 0.05) both individually and in complex interactions, which affect the accuracy of quantitative concentrations obtained from DBS samples for each compound on each card type.Conclusion: To achieve the acceptance criteria (±15%) for accuracy when removing a portion of the DBS spot for quantitative analysis, HCT and punch location for each selected card type will need to be assessed during validation and sample analysis.